Cover Feature: Suppressing Electrode Crosstalk and Prolonging Cycle Life in High‐Voltage Li Ion Batteries: Pivotal Role of Fluorophosphates in Electrolytes (ChemElectroChem 13/2022). Issue 13 (9th June 2022) - Klein, Sven; Haneke, Lukas; Harte, Patrick; Stolz, Lukas; van Wickeren, Stefan; Borzutzki, Kristina; Nowak, Sascha; Winter, Martin; Placke, Tobias; Kasnatscheew, Johannes
Abstract : The Cover Feature illustrates a Li ion battery with enhanced cell voltage as a well‐known pragmatic strategy to enhance energy density and performance. However, this measure is compromised by decreased cycle life, predominantly as a result of transition metal (TM) dissolution from cathode and deposition on anode (=electrode crosstalk), which finally triggers an inhomogeneous Li plating ( e.g . Li dendrites), thus capacity losses and even short‐circuits. Fluorophosphates (Lix POy Fz ) can scavenge TMs and relevantly enhance cycle life, though, its concentration is crucial for performance and sensitively depends on applied cell materials. More information can be found in the Research Article by S. Klein et al .